Simultaneous multislice inversion contrast imaging using power independent of the number of slices (PINS) and delays alternating with nutation for tailored excitation (DANTE) radio frequency pulses - Koopmans, P; Boyacioǧlu, R; Barth, M; Norris, D (2013)
A method for simultaneous multislice (SMS) inversion contrast imaging is presented using a combination of the delays alternating with nutation for tailored excitation (DANTE) and the power independent of the number of slices (PINS) techniques. In SMS imaging, simultaneously excited slices result in an aliased image that is disentangled using parallel imaging reconstruction techniques. At high-magnetic field strengths, the peak amplitude and specific absorption rate of conventional (summed) SMS radio frequency pulses can be prohibitively high. Using the PINS approach, specific absorption rate is independent of the number of slices allowing high SMS acceleration factors even at high fields. Using DANTE, adiabatic SMS radio frequency pulses can be created to be combined with PINS. This allows 2D imaging protocols that employ adiabatic pulses to also reap the benefits of low specific absorption rate SMS acceleration. As a proof-of-concept, simulations and measurements using hyperbolic secant inversion pulses are shown. © 2012 Wiley Periodicals, Inc.